2013
DOI: 10.1088/0957-4484/25/3/035703
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise in individual carbon nanotube field-effect transistors with top, side and back gate configurations: effect of gamma irradiation

Abstract: We report on the influence of low gamma irradiation (10(4) Gy) on the noise properties of individual carbon nanotube (CNT) field-effect transistors (FETs) with different gate configurations and two different dielectric layers, SiO2 and Al2O3. Before treatment, strong generation-recombination (GR) noise components are observed. These data are used to identify several charge traps related to dielectric layers of the FETs by determining their activation energy. Investigation of samples with a single SiO2 dielectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…Noise spectroscopy on our field effect transistor devices built from pristine CNTs revealed several defect levels in the SiO 2 of our substrates. The smallest trap activation energy we found was E a = 62 meV . Temperature and bias voltage in our experiments are much too low to supply the necessary energy.…”
Section: Resultscontrasting
confidence: 55%
“…Noise spectroscopy on our field effect transistor devices built from pristine CNTs revealed several defect levels in the SiO 2 of our substrates. The smallest trap activation energy we found was E a = 62 meV . Temperature and bias voltage in our experiments are much too low to supply the necessary energy.…”
Section: Resultscontrasting
confidence: 55%
“…The spin lifetime is very likely still influenced by charge traps in the SiO 2 . Suspending the CNTs or low dose gamma irradiation, which is known to remove traps in the oxide and to improve the performance of CNT-based field-effect transistors [80], would be expected to enhance the spin lifetime. The diameter of the CNT used for the Hanle measurements was 1.5 nm, giving rise to a spin-orbit coupling strength in the order of 1 meV [81].…”
Section: Spin Precession Within Carbon Nanotubesmentioning
confidence: 99%
“…Cranial irradiation, even a single moderate dose, leads to massive neural stem cell death (Fukuda et al, 2004) followed by changes in cell metabolism, the cellular microenvironment, cell proliferation, and tissue shape as well as long-term cognitive impairments and growth reduction (Sydoruk et al, 2014; Walenta and Mueller-Klieser, 2016). Our previous results showed that selective Atg7 deficiency reduced neural stem cell death at 6 h after irradiation.…”
Section: Discussionmentioning
confidence: 99%